Inter-formation dans le cadre d’un partenariat éducatif - Catherine Mathey-Pierre; Edith Waysand (Sociétés et Jeunesses en Difficulté)
This paper describes a successful experiment of partnership among educational professionals, namely between teachers and street educators, in a junior high-school of an underprivileged urban area. First, the scheme which was implemented to drive all pupils to success is firstly exposed. Secondly, we shed the light on the conditions which allowed the scheme to last several years and those that let it to its termination. The exceptional nature of such a collective endeavour and its fragility are pointed out. Overall, the article highlights that professionals do not benefit from enough institutional support for handling the problems they face.